Pemberdayaan Ibu-Ibu PKK melalui Pelatihan Membatik Taplak Meja Berbasis Kearifan Lokal di Kecamatan Merakurak - Inarotul A'yun; Nur Hidayatul Istiqomah; Siti Ulin Ni’mah Mz; Syahrotul Maghfiroh (Journal of Innovation and Contribution to Community Service, 2025)
This research aims to empower women from the Family Welfare Movement (PKK) in Merakurak District through training in batik tablecloths based on local wisdom. This activity is designed not only to improve technical batik skills but also to encourage social, economic, and cultural transformation among village women. The method used is qualitative research with a Participatory Action Research (PAR) approach, which positions participants as active subjects throughout the training process, from needs identification and implementation to evaluation and follow-up. The results demonstrate that this training effectively enhanced participant engagement, creativity, and self-confidence. Furthermore, the integration of local motifs into batik works helps strengthen cultural identity and provides added economic value. This training also opens up opportunities for the formation of joint business groups and digital marketing, making it a sustainable model of community-based women's empowerment worthy of replication in other areas